Mt. Whitney: Determinants of summit success and acute mountain sickness - Wagner, D. R.; D'Zatko, K.; Tatsugawa, K.; Murray, K.; Parker, D.; Streeper, T.; Willard, K. (Medicine & Science in Sports & Exercise, 2008)
Purpose: The aim of this study was to determine the prevalence of summit success and acute mountain sickness (AMS) on Mt. Whitney (4419 m) and to identify variables that contribute to both.